THE POETICS OF LANDSCAPE IN THE MILITARY WORKS BY MARKO CHEREMSHYNA AND HRYHORII KOSYNKA - Чобанюк, В. Я. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article examines the poetics of landscape in Marko Cheremshyna's and Hryhorii Kosynka's novellas about the war in the light of national traditions and their own aesthetic views and the writers’ worldview orientations.